Studies on suspension cultures of lymphoid cells infected with Theileria annulata (Dschunkowsky and Luhs 1904) - Shad-Del, Fazlollah (The University of Edinburgh, 1977)
TheUeria an ,plat, infection is a tick -borne protozoal disease of cattle. The high mortality and lack of any effective treatment make this disease one of great economic importance. The success achieved in adaptation of the parasite to culture in vitro facilitated investigation of the disease and the consequent attenuation of the parasite led the production of experimental vaccines. The literature relevant to the aspects studied was reviewed. Methods of isolation and adaptation of strains of the parasite in tissue culture were compared. A simple and new method of isolation from whole blood was introduced. The first isolation of a very virulent strain in tissue culture was achieved. Growth rates of five strains of T. annulate in vitro showed an inverse relationship between rate of growth and virulence of strain. Several growth media and supplements were compared and the most satisfactory were shown to be Eagle's MEM with calf serum, lactalbumin hydrolysate and yeast extract. Growth of T. annulata- infected cells in various conditions was measured and factors affecting it were investigated. Of these, pH of the medium and percentage of viable cells in suspension were very important. For morphological studies, from several methods of preparation of smears and staining, a modified method of linear smears was adopted. The morphology of the macroschizont and nuclear particles in the host cells was studied. Various factors including developmental changes of the macroschizont were demonstrated. Attempts to infect normal bovine cells with schizonts in vitro using infected cells and freed parasites and to infect calves with separated schizont particles were unsuccessful. Establishment of cell lines from normal bovine leucocytes and lymphoid cells using mitogens failed. The amounts of glucose uptaken and lactate produced in the culture of schizont -infected cells were measured and these correlated with cell growth. A surplus of glucose in growth medium did not affect its utilisation by the infected cells. The methods for cryopreservation of T. annulata- infected cells were investigated. The cryoprotectants used, the methods of freezing and thawing, the duration of viability of the infected cells in low temperature storage and re- establishment of the cells after preservation at low temperatures were studied.